Psychosocial Impact of Cancer Care Disruptions in Women With Breast Cancer During the COVID-19 Pandemic - Soriano, Emily C.; Perndorfer, Christine; Otto, Amy K.; Fenech, Alyssa L.; Siegel, Scott D.; Dickson-Witmer, Diana; Clements, Lydia; Laurenceau, Jean-Philippe (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic caused significant disruptions in cancer care, and preliminary research suggests that these disruptions are associated with increased levels of psychosocial distress among cancer survivors. The purpose of this study was to offer a descriptive report of the psychosocial functioning, perceived risk and fear of cancer progression, and COVID-19 pandemic impact and experiences in a unique, high-risk patient cohort: breast cancer survivors whose cancer treatment was delayed and/or changed due to the COVID-19 pandemic. Methods: This cross-sectional study included 50 women with DCIS, LCIS, or invasive breast cancer whose cancer surgery was postponed due to the pandemic. As they awaited delayed surgery or shortly after they received delayed surgery, participants completed questionnaires on psychosocial functioning (depression, anxiety, sleep, quality of life), their perceived risk and fear of cancer progression, patient-provider communication about disruptions in their care, personal impact of the pandemic, worry/threat about COVID-19, and COVID-19 symptoms/diagnoses. Descriptive statistics and bivariate correlations were computed among continuous study variables. Independent samples t-tests explored group differences in psychosocial functioning between survivors who were still awaiting delayed surgery and those who had recently received it. Results: Overall, the sample denied that the pandemic seriously negatively impacted their finances or resource access and reported low-to-moderate levels of psychosocial distress and fear about COVID-19. Twenty-six percent had clinically significant levels of fear of cancer progression, with levels comparable to other recent work. About a third were still awaiting delayed cancer surgery and this group reported lower satisfaction with communication from oncology providers but overall did not seem to report more psychosocial difficulties than those who already had surgery. Conclusions: Shortly before or after primary breast cancer surgery that was delayed due to the COVID-19 pandemic, this sample of survivors appears to be generally managing well psychosocially. However, many psychosocial difficulties (e.g., fear of cancer recurrence/progression) typically have an onset after the completion of treatment, therefore, research should continue to follow this cohort of cancer survivors as the pandemic’s direct impact on their care likely increases their risk for these difficulties later in survivorship.